Strategi Kepemimpinan Kepala Sekolah dalam Menghadapi Revolusi Digital 4.0 - Khanif Kurniawan; Kusumawati Kusumawati; Silvi Dwi Hurriyati; Ade Fathi Amirrasyid; Mugni Mugni (Journal on Education, 2023)
Technological developments become familiar and have an impact on society. The Digital Industrial Revolution 4.0 has had a significant impact on people's lives, one of which is in the world of Education. So, leadership is needed that can adjust and take advantage of this technological development. At the school level, a principal becomes one of the important components in moving the wheels of Education in schools. Therefore, a school principal needs to develop a strategy in the face of changes in this Industrial Revolution 4.0. This study aims to find out how the strategies prepared by school principals in the face of the Industrial Revolution 4.0. The method used in this study is qualitative location is the place of this study is SD Negeri 1 Kamarang, Greged District Cirebon Regency. Data collection techniques in this study use interviews, and observations, and involve documentation. The results of this study concluded that the principal in SD Negeri 1 Kamarang prepare five strategies in the face of the Industrial Revolution 4.0 including a) Improvement of the infrastructure in the field of ICT b) openness with the development of the digital era 4.0; d) process and result oriented; e) mastering the 4C formula, namely: critical thinking, creativity, communication, collaboration.